Evaluation of osmotic fragility of erythrocytes in dystocia affected buffaloes - PRABHAKAR, S; NANDA, A S; GHUMAN, S P S (The Indian Journal of Animal Sciences, 2013)
Susceptibility of erythrocytes to osmotic stress is increased near parturition due to variable endocrine milieu. Possibility of comparatively morc increase in fragility of erythrocytes in dystocia affected buffaloes is needed to be ascertained. Osmotic resistance of erythrocytes was evaluated in 26 dystocia affected buffaloes subjected to fetatomy or caesarean section. Blood samples were collected before treatment and then at 24 hr interval for 2 days. Minimum and maximum hacmolysis of erythrocytes and mean corpuscular fragility was determined in different concentrations of saline solutions. Osmotic fragility values of6 calving buffaloes on 6 peripartal days served as controls. Erythrocytes in controls were least resistant on the day of calving than the peripartal days. In dystocia affected buffaloes, initial and maximum haemolysis values showed the erythrocytes to be less resistant to osmotic stress as compared to controls. On post-manoeuvring days, erythrocytes in buffaloes that either survived or died following caesarean operation were more fragile than the fetotomy group.